2015
DOI: 10.1038/cddis.2015.173
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Mdmx to treat breast cancers with wild-type p53

Abstract: The function of the tumor suppressor p53 is universally compromised in cancers. It is the most frequently mutated gene in human cancers (reviewed). In cases where p53 is not mutated, alternative regulatory pathways inactivate its tumor suppressive functions. This is primarily achieved through elevation in the expression of the key inhibitors of p53: Mdm2 or Mdmx (also called Mdm4) (reviewed). In breast cancer (BrCa), the frequency of p53 mutations varies markedly between the different subtypes, with basal-like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
60
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(67 citation statements)
references
References 49 publications
6
60
1
Order By: Relevance
“…High MDM4 levels were found to be a feature of WT p53 BCs, as demonstrated in luminal subtypes. Basal‐like biopsies in our mixed BC subtype tissue microarray (TMA) also stained intensely for p53, which is generally indicative of p53 mutations, coincident with high MDM4 levels . To expand this finding, a TMA of 87 biopsies derived from basal‐like BC (the majority of which have a TNBC phenotype ) was stained by IHC for p53 and MDM4 (Figure ).…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…High MDM4 levels were found to be a feature of WT p53 BCs, as demonstrated in luminal subtypes. Basal‐like biopsies in our mixed BC subtype tissue microarray (TMA) also stained intensely for p53, which is generally indicative of p53 mutations, coincident with high MDM4 levels . To expand this finding, a TMA of 87 biopsies derived from basal‐like BC (the majority of which have a TNBC phenotype ) was stained by IHC for p53 and MDM4 (Figure ).…”
Section: Resultsmentioning
confidence: 77%
“…Our study shows strategic vulnerability in the dependency of BC with mutant p53 on the expression of MDM4, a key negative regulator of p53. We have recently reported that MDM4 is highly expressed in a large proportion of luminal BCs, which mainly have WT p53 . This high expression of MDM4 can be rationalized in BCs expressing WT p53.…”
Section: Discussionmentioning
confidence: 94%
“…It is noteworthy that our research uncovers several E3 ligases, such as PML FBXO5, MALT1 and MDM4, as potential EMT regulators despite their TNBC- associated gene mutations are not as common as RNF8 (Figure S1C). FBXO5 (also known as FBX5 and Emi1), MALT1 and MDM4 have been reported as therapeutic targets for breast cancer (Haupt et al, 2015; Pan et al, 2016; Wang et al, 2014). Even though PML is a legitimate tumor suppressor in leukemia, it has been shown to be upregulated in breast cancer in which PML facilitates fatty acid metabolism to support breast cancer survival (Carracedo et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…). Because DNA damage induces p53 protein accumulation and p53‐dependent apoptosis, we next examined the possible regulation of p53 expression by CITED2 under chemotherapy in MCF‐7 cells with wild‐type p53 …”
Section: Resultsmentioning
confidence: 99%